The Usulan Strategi Optimalisasi Produktivitas Menggunakan Metode Objective Matrix dan Marvin E Mundel (Studi kasus: PT XYZ) - Wungguli, Fauzan; Rasyid, Abdul; Uloli, Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to measure and improve the productivity of PT XYZ using the Marvin E. Mundel and Objective Matrix (OMAX) methods. The research was conducted through interviews and observations of the company's operations in 2023-2024. The Marvin E. Mundel method calculates the productivity index (IP) by comparing outputs (electricity sales, equipment rental, repair services, installation, government subsidies) and inputs (operations, maintenance, salaries), resulting in an initial IP of 93.516, which decreased due to a shortage of fleets and devices. The strategy of adding 2 fleets, 3 devices, and a budget increased the IP to 100.113 (up 7%). The method identified user complaints (4,203 cases) as the top priority (weight 0.78), with a productivity index of 16% in January 2024. Recommendations include optimizing complaint handling, staff training, and real-time monitoring technology.